Pengaruh Kepuasan Kerja, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus PT. ISS Indonesia Cabang Medan) - Hasanah, Fitria; Fitiani Dewi, Ananda (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Employee performance is proof that employees can do their jobs on time with the knowledge they have. This study aims to find out and analyze the effect of job satisfaction, work motivation, and work discipline on employee performance. The method used in this study is a quantitative method with data collection techniques used in the form of primary data where data is collected using questionnaires. This research was conducted on permanent employees of PT. ISS Indonesia Medan Branch with a sample of 60 respondents. The results of the analysis show that partially job satisfaction, work motivation and work discipline have a positive and significant effect on the performance of PT. ISS Indonesia Medan Branch. Then the results of the analysis proved that simultaneously job satisfaction, work motivation and work discipline have a positive and significant effect on the performance of PT. ISS Indonesia Medan Branch.